Pendampingan Dan Pengembangan SDM Anak Yatim Perempuan Pada Aspek Kreativitas Berbasis Bioentrepreneurship - Ahmad Rosidi; Zainal Arifin (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Mentoring and developing human resources (HR) for female orphans in aspects of entrepreneurship-based creativity is very important in facilitating personal growth and professionalism of human resources. The main focus of this program is to develop skills and knowledge in entrepreneurship based on biological resources and encourage creativity to create sustainable economic opportunities. The mentoring method uses the ABCD (Asset Based Community Development) method, implemented in the LKSA Yabappenatim Community. Based on the empowerment results, it can be concluded that empowerment in improving female orphans in the aspect of utilizing environmental waste as valuable materials and developing the creativity of female orphans based on entrepreneurship will not be successful if there is no cooperation and active participation from the mentoring subjects, the community, especially the surrounding community. Associations and institutions related to the LKSA Yabappenatim institution and donors who have contributed sincerely to implementing this program in the LKSA Yabappenatim community. The implementation of empowerment runs optimally because this empowerment results in the development of the creativity of female orphans based on entrepreneurship in utilizing natural environmental waste around LKSA Yabappenatim into valuable materials or products.